2018
DOI: 10.1016/j.toxicon.2017.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Substrate cleavage and duration of action of botulinum neurotoxin type FA (“H, HA”)

Abstract: Botulinum neurotoxin (BoNT) type FA is the only known naturally occurring chimeric BoNT of domains of BoNT/A and BoNT/F. BoNT/FA consists of an F5-like light chain (LC), a unique heavy chain (HC) translocation domain, and a HC receptor binding domain similar to BoNT/A1. Previous analyses of purified BoNT/FA have indicated a 5-10-fold greater potency in cultured human or rat neurons as compared to BoNT/A1 and a 400-500-fold greater potency compared to BoNT/B1. However, in vivo potency in mice was about 5-fold l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…Botulinum neurotoxins comprise a large family of protein toxins, with seven neurotoxic serotypes and several subtypes as well as chimeric toxins . While all BoNTs cause botulism, variation in potency, clinical presentation, duration of action, species specificity, and cell entry properties vary for different BoNT serotypes . These variations could be due to differences in LC activity, specific cell association, or entry of the LC into the cell's cytosol and intracellular trafficking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Botulinum neurotoxins comprise a large family of protein toxins, with seven neurotoxic serotypes and several subtypes as well as chimeric toxins . While all BoNTs cause botulism, variation in potency, clinical presentation, duration of action, species specificity, and cell entry properties vary for different BoNT serotypes . These variations could be due to differences in LC activity, specific cell association, or entry of the LC into the cell's cytosol and intracellular trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…[8]. While all BoNTs cause botulism, variation in potency, clinical presentation, duration of action, species specificity, and cell entry properties vary for different BoNT serotypes[7,17,31,[56][57][58][59][60][61][62][63][64]. These variations could be due to differences in LC activity, specific cell association, or entry of the LC into the cell's cytosol and intracellular trafficking.…”
mentioning
confidence: 99%
“…Potency determinations of different BoNTs by NCB assay and MBA do not necessarily correlate. Several BoNT types (A2, A6, FA) have been shown to enter cultured neurons more efficiently, but BoNT/FA was significantly less potent in mice [55,57,61,126,127]. Thus, greater potency of a BoNT in NCB assays doesn't necessarily mean greater toxicity in vivo.…”
Section: Critical Considerations For Bont Detection By Cell-based Assaysmentioning
confidence: 99%
“…For these applications, an assay that can detect the biologic activity of multiple BoNT seroand sub-types is required. While cell-based assays can provide human-specific and highly sensitive BoNT detection platforms fulfilling this requirement, research in the past few years has indicated that the activity of BoNTs in cultured neurons and in vivo in mice does not equally correlate for all BoNTs [55,57,61,126,128]. Thus, the mouse bioassay remains an important detection method for BoNTs, in particular, for investigations of novel BoNTs and for detection of BoNTs in complex matrices such as stool samples and food matrices.…”
Section: Critical Considerations For Bont Detection By Cell-based Assaysmentioning
confidence: 99%
See 1 more Smart Citation